2006
DOI: 10.1007/bf03022793
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nabilone, a synthetic cannabinoid, on postoperative pain

Abstract: Purpose:Cannabinoids have been shown to have analgesic properties in animal studies, but a potential role for these drugs in acute pain management has not been established. It was hypothesized that nabilone, an oral cannabinoid synthetic tetrahydrocannabinol analogue, decreases morphine consumption, pain scores, nausea and vomiting following major surgery. Methods:A double-blind, randomized, placebo-controlled, parallel-group pilot trial compared the effects of two different doses, 1 mg (n = 11) and 2 mg (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 15 publications
5
127
0
4
Order By: Relevance
“…Correct dosing will also be important. Indeed, a dose of nabilone of 2 mg three times daily was associated with an increase in pain scores in a trial of postoperative pain (43).…”
Section: Ajulemic Acid (Aja Ct3 Ip751)mentioning
confidence: 99%
“…Correct dosing will also be important. Indeed, a dose of nabilone of 2 mg three times daily was associated with an increase in pain scores in a trial of postoperative pain (43).…”
Section: Ajulemic Acid (Aja Ct3 Ip751)mentioning
confidence: 99%
“…In view of these attributes, we have argued that assays of pain-depressed behavior may complement conventional assays of pain-stimulated behavior and increase the predictive validity of preclinical candidate analgesic assessment (Negus et al, , 2010a. Given the poor efficacy of THC and other cannabinoid receptor agonists to treat acute pain in humans (Raft et al, 1977;Buggy et al, 2003;Naef et al, 2003;Beaulieu, 2006;Kraft et al, 2008;Klooker et al, 2011) we predicted that THC and CP55940 would not produce antinociception in assays of acute pain-depressed behavior in rats despite the apparent efficacy of these drugs in standard assays of pain-stimulated behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies using dronabinol, nabilone, and levonantradol demonstrated benefit, but their methodologies were not as rigorous as in more recent trials, and so the benefits might have been overestimated 36 . The few trials using cannabinoids in acute pain have shown essentially no benefit, and present recommendations are against cannabinoid use in the postoperative setting [37][38][39] .…”
Section: Painmentioning
confidence: 91%